Mögliche Dialektmerkmale in den Personennamen des Mittleren Reiches - Ilin-Tomich, Alexander (Zeitschrift für ägyptische Sprache und Altertumskunde, 2018)
The paper discusses three irregularities in the regional distribution of personal names in Middle Kingdom sources, which may be linked to regional language varieties. One feature, the sound change , occurs predominantly in sources from the Memphis-Faiyum region. The two other features, the use of the negative word and the possessive prefix , are confined to Theban and Southern Upper Egyptian sources. The latter two features become standard in Late Egyptian; thus, the evidence presented in the paper contributes to the discussion on the possible dialectal status of Late Egyptian during the Middle Kingdom.